# algebra

Prove by mathematical induction that x^2n - y^2n has a factor of x+y.

My answer is incomplete since i do not know what to do next. here it is:

i.) for n=1

x^2(1) - y^2(1) = x^2 - y^2
= (x+y)(x-y)

ii.) Assume that the proposition is true for all n=k, that is, x^2k - y^2k has a factor of x+y for all k¡Ý1.

iii.) n=k+1

x^2(k+1) - y^2(k+1)
=x^2k+2 - y^2k+2
=x^2k ¡ñ x^2 - y^2k ¡ñ y^2
=(tthis part I don't know)

I hope you can help me. Thanks!

1. 👍
2. 👎
3. 👁

## Similar Questions

1. ### Math

Use Mathematical Induction to show that the statement 2 + 6 + 10 + . . . + (4n – 2) = 2n^2 is true

2. ### MATh

Prove by mathematical induction that 1+3+5+7+......+(2n-1)=n²

3. ### Mathematical Induction

Use mathematical induction to prove that the following is true. 8+11+14...+(3n+5)=1/2n(3n+13), for all n in the set of natural numbers.

4. ### Math

Use mathematical induction to prove that 5^(n) - 1 is divisible by four for all natural numbers n. Hint: if a number is divisible by 4, then it has a factor of 4. also, -1 = -5 +4 This is a take home test so I don't want the

1. ### Math..mathematical induction

Prove by mathematical induction that 1+3+5+7+....+(2n-1)=n²

2. ### Mathematical induction. I'm stuck. So far I have..

For all integers n ≥ 1, prove the following statement using mathematical induction. 1+2^1 +2^2 +...+2^n = 2^(n+1) −1 Here's what I have so far 1. Prove the base step let n=1 2^1=2^(1+1)-1 False. Someone else suggested that the

3. ### precalculus

Find Pk + 1 if Pk = 7 + 13 + 19 + ...+[6(k - 1)+1] + (6k + 1) 7 + 13 + 19 + …+[6(k - 1) + 1] + (6k + 1) + [6(k + 1) + 1] 8 + 14 + 20 + …+[7(k - 1) + 1] + (7k + 1) 7 + 13 + 19 + …+(6k + 1) 7 + 13 + 19 + ...+[6(k - 1) + 1] +

4. ### math

Using Mathematical Induction, prove the following: a) 6^n - 1 is divisible by 5, for n>_0.

1. ### Maths

n(n+1)(n+5)is a multiple of 3 proove it by mathematical induction.

2. ### precalculus

Can you please check my answers? 1.Find Pk + 1 if Pk=2^K-1/k! answer: 2^k+1/(k+1)! 2.Find Pk + 1 if Pk = 7 + 13 + 19 + ...+[6(k - 1)+1] + (6k + 1) answer: 7+13+9...(6k-1+1)+6k+1 +(6k+2) 3.What is the first step when writing a

3. ### Discrete Math

Use mathematical induction to prove the truth of each of the following assertions for all n ≥1. n³ + 5n is divisible by 6 I really do not understand this to much. This is what I have so far: n = 1, 1³ - 5(1) = 6, which is

4. ### Maths

Using Mathematical Induction, prove the following: a) 2+4+6+.....+2n= n(n+1)